EFEKTIVITAS PENAMBAHAN PERASAN CABAI MERAH (Capsicum annum) TERHADAP PERTUMBUHAN DAN INTENSITAS WARNA MERAH IKAN KOMET (Carassius auratus) - Anis Zubaidah; Ganjar Adhywirawan Sutarjo; Hikmah Perwita Sari (Universitas Muhammadiyah Malang, 2024)
The quality of ornamental goldfish is highly influenced by body color brightness, which depends on carotenoid content. Since fish cannot synthesize carotenoids naturally, supplementation through feed is required to enhance pigmentation. Cayenne pepper is a natural carotenoid source that has potential to improve fish coloration. This study aimed to evaluate the effect of cayenne pepper extract supplementation on the red color intensity, growth, and survival rate of Comet goldfish. The research employed an experimental method using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments consisted of different cayenne pepper extract concentrations in feed: 0% (control), 1%, 3%, and 5%. Comet goldfish with an average size of ±6 cm were stocked at a density of 10 fish per aquarium and fed three times daily at 5% of biomass. Water quality management, including siphoning and partial water exchange, was conducted every three days. The results showed that cayenne pepper supplementation significantly improved the red color intensity of Comet goldfish. The highest color intensity was obtained in the 5% treatment (22.77 ± 4.96). The highest length growth was also recorded in the 5% treatment (0.50 ± 0.13 cm), while the highest weight gain was observed in the 3% treatment (1.43 ± 0.07 g). The highest survival rate was achieved in the 5% treatment (96.67%). Water quality remained within suitable ranges throughout the study. These findings indicate that 5% cayenne pepper supplementation effectively enhances coloration, growth, and survival of Comet goldfish.